The current landscape of immunotherapy for pediatric brain tumors - Hwang, Eugene; Sayour, Elias J.; Flores, Catherine T.; Grant, Gerald; Wechsler-Reya, Robert; Hoang-Minh, Lan B.; Kieran, Mark W.; Salcido, Joanne; Prins, Robert M.; Figg, John W.; Platten, Michael; Candelario, Kate M.; et al. (Nature cancer, 2022)
Pediatric central nervous system tumors are the most common solid malignancies in childhood, and aggressive therapy often leads to long-term sequelae in survivors, making these tumors challenging to treat. Immunotherapy has revolutionized prospects for many cancer types in adults, but the intrinsic complexity of treating pediatric patients and the scarcity of clinical studies of children to inform effective approaches have hampered the development of effective immunotherapies in pediatric settings. Here, we review recent advances and ongoing challenges in pediatric brain cancer immunotherapy, as well as considerations for efficient clinical translation of efficacious immunotherapies into pediatric settings.
Gesehen am 30.03.2023